PENGARUH TERAPI ZINGER OFFICINALE TERHADAP INTENSITAS NYERI LOW BACK PAIN DI POSYANDU MARGOMULYO DESA NGRANCAH KECAMATAN GRABAG - MARGONO MARGONO (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: to analyze the effect of Zingiber officinale to decrease the level of pain in patients with Low Back Pain (LBP). Methods: This study design is Quasi Experiment with using the draft